2013
DOI: 10.1080/15320383.2013.786021
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Assessment of Two Excavated Mass Graves in Rwanda: A Pilot Study

Abstract: Necrosols are a unique category of anthropogenic soils that are associated with excavated cemeteries or graveyards. In spite of the growing number of cemeteries and burial sites found across urban and rural areas globally, scientific information regarding the contamination potential of this category of soils is relatively scarce and not properly understood. The purpose of this study is to fill this gap by assessing the contamination significance of trace metal contents in the necrosols associated with two exca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…The soils of cemeteries A, B and C were collected, in 5 internal points and in the external area of the cemeteries spaced every 100 m. The soils were sampled at two depths, from 0 to 20 and 20 to 40 cm; with three levels of repetition, totaling 180 samples between the cemeteries A, B and C to evaluate the concentrations of Fe, Mn, Cu, Zn, Cr and Pb (g kg −1 ), which were found to be more prevalent in studies involving the soil of cemeteries (Amuno & Amuno, 2013 ; Jonker & Olivier, 2012 ; Kemerich et al, 2014 ; Natali et al, 2016 ; Neckel et al, 2016 , 2021 ; Neira et al, 2008 ; Shafer et al, 2008 ; Silva et al, 2020 ; Spongberg & Becks, 2000 ), with the exception of iron, was not analyzed among these studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The soils of cemeteries A, B and C were collected, in 5 internal points and in the external area of the cemeteries spaced every 100 m. The soils were sampled at two depths, from 0 to 20 and 20 to 40 cm; with three levels of repetition, totaling 180 samples between the cemeteries A, B and C to evaluate the concentrations of Fe, Mn, Cu, Zn, Cr and Pb (g kg −1 ), which were found to be more prevalent in studies involving the soil of cemeteries (Amuno & Amuno, 2013 ; Jonker & Olivier, 2012 ; Kemerich et al, 2014 ; Natali et al, 2016 ; Neckel et al, 2016 , 2021 ; Neira et al, 2008 ; Shafer et al, 2008 ; Silva et al, 2020 ; Spongberg & Becks, 2000 ), with the exception of iron, was not analyzed among these studies.…”
Section: Methodsmentioning
confidence: 99%
“…This aspect refers to the prediction analysis of COVID-19 deaths to obtain the world parameters of burials. The incidence of fatal cases of COVID-19 justifies rethinking the structure of cemeteries, so that they can account for the concentration of metals deposited in the soil (Amuno & Amuno, 2013 ; Jonker & Olivier, 2012 ; Kemerich et al, 2014 ; Natali et al, 2016 ; Neckel et al, 2016 , 2021 ; Neira et al, 2008 ; Shafer et al, 2008 ; Silva et al, 2020 ; Spongberg & Becks, 2000 ). A seasonal univariate modeling time series using autoregressive integrated moving average (ARIMA) was applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This leachate is characterized by high BOD, pH, conductivity and chemical compounds including phosphorus, nitrogen, Na + , Ca 2+ , Cl − , , and 10% organic compounds [ 18 , 53 ]. Necrosols also have the possibility to be contaminated with heavy metals such as Pb, Cr, Zn, As, Mo, and Cu through the decomposition of paints, preservatives and metallic components from coffins [ 54 , 55 ] Amuno [ 31 ] found slightly higher concentrations of 12 trace elements (As, Ba, Cr, Cs, Ga, Ni, Rb, Sc, Th, V, Y, and Zr) in soil of mass grave sites in Rwanda compared to offsite soils. However, that study revealed that the elemental concentrations were not great enough to generate any environment concern.…”
Section: Disposal Events and Technologies For Carcasses And Corpsesmentioning
confidence: 99%
“…En el estudio de suelos de fosas comunes excavadas en Ruanda, encuentran que las concentraciones media y máxima en los sitios de arsénico (As), bario (Ba), cromo (Cr), cesio (Cs), galio (Ga), níquel (Ni), rubidio (Rb), escandio (Sc), torio (Th), vanadio (V), y zirconio (Zr), son generalmente más altas que sus valores fuera del sitio y que los contenidos de metales traza de los suelos del cementerio presentan una mayor proporción de acumulación para ciertos elementos, particularmente As, Cr, Ni y Cs en relación con los promedios mundiales para los suelos [17,18] Además, el estado de contaminación actual de los Necrosoles como resultado de la entrada antropogénica de Cr y Pb por los proyectiles de bala presentes en los cráneos sepultados en el sitio; es de particular interés para estos estudios, la cantidad de sales solubles, específicamente de sodio, que también pueden proliferar causando la sodicidad del suelo [19][20].…”
Section: Propiedades Químicasunclassified